(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research examines the role of the knowledge economy in knowledge production within the business administration departments at Shaqra University. The study’s central hypothesis is that the knowledge economy plays a positive role in knowledge production within these departments during the period 1446-2025. The study population comprises all faculty members working in the business administration departments at Shaqra University, including those holding teaching and research positions across various administrative disciplines such as business administration, marketing, finance, and accounting. This population is considered suitable for the study due to the direct involvement of its members in knowledge production through scientific research, teaching, and participation in academic activities. This reflects the reality and role of the knowledge economy within the university environment at Shaqra University in the Kingdom of Saudi Arabia. The study sample was selected using stratified random sampling to ensure representation of all disciplines within the various business administration departments at the university. The questionnaire included 35 faculty members. The results showed that the overall mean score for the availability of knowledge economy elements was (4.11) with a standard deviation of (0.73), for meeting the requirements of the knowledge economy it was (4.12) with a standard deviation of (0.71), for the college or department’s orientation towards the characteristics of the knowledge economy it was (4.15) with a standard deviation of (0.72), and for the benefits of the knowledge economy orientation it was (4.14) with a standard deviation of (0.60). This indicates a very high level of agreement among the sample. The probability value of the regression coefficient (0.000sig = 0.05) is less than the significance level (0.05), indicating a statistically significant relationship between the availability of knowledge economy elements and the knowledge level within the college. There are statistically significant differences in the perception of the knowledge economy and its role in knowledge production attributable to the gender variable (male/female) and the job level variable (excluding years of experience). The study recommended strengthening the integration of scientific research with societal needs, establishing flexible and innovation-oriented research frameworks, implementing systems that support intellectual property, ensuring fairness in protecting the rights of knowledge producers, and comprehensively activating the knowledge economy within the college or department to stimulate knowledge development.